Identification of kaempferol as an OSX upregulator by network pharmacology-based analysis of qianggu Capsule for osteoporosis - Huang, Ann Yehong; Xiong, Zhencheng; Liu, Kuankuan; Chang, Yanan; Shu, Li; Gao, Guolan; Zhang, Chi (Frontiers in Pharmacology, 2022)
Osteoporosis is the most common metabolic disease of skeleton with reduced bone density and weaker bone. Qianggu Capsule as a traditional chinese medicine has been widely used to treat osteoporosis. The potential pharmacological mechanism of its active ingredient Gusuibu is not well understood. The purpose of this work is to analyze the anti-osteoporosis function of Gusuibu based on network pharmacology, and further explore the potential mechanism of Qianggu Capsule. The active compounds and their corresponding targets of Gusuibu were obtained from TCMSP, TCMID, and BATMAN-TCM databases. Potential therapeutic targets for osteoporosis were obtained through DisGeNET, TTD, GeneCards, MalaCards, CTD, and OMIM databases. The overlapping targets of Gusuibu and osteoporosis were obtained. GO and KEGG pathway enrichment analysis were performed. The “Gusuibu-active compounds-target genes-osteoporosis” network and protein-protein interaction (PPI) network were constructed, and the top hub genes were screened by using the plug-in CytoHubba. Molecular docking was used to verify the binding activity of hub genes and key compounds. We identified 21 active compounds and 140 potential therapeutic targets that may be related to Gusuibu and 10 hub genes (AKT1, IL6, JUN, TNF, MAPK3, VEGFA, EGFR, MAPK1, CASP3, PTGS2). Molecular docking analysis demonstrated that four key active small molecules in Gusuibu (including Luteolin, Naringenin, Kaempferol, and Beta-sitosterol) have excellent binding affinity to the target proteins encoded by the top 10 hub genes. Our new findings indicated that one key active compound kaempferol activated the expression of osteoblast specific transcription factor OSX through JNK kinase pathway.